The reading interests of college students in Central Luzon State University - San Juan, Nuelah F.
This study sought to determine the reading interest of college students in Central Luzon State University. Specifically, it aimed to : 1) find out if the students read other reading materials aside from their textbooks and reference books ; 2) identify the various types of reading materials read by them ; 3) find out what factors significantly influence their reading interests ; 4) identify the sources of the different reading materials ; and 5) to find out what subject matter/content of materials they like to read about.